Research Progress of High‐Performance Organic Material Pyrene‐4, 5, 9, 10‐Tetraone in Secondary Batteries. Issue 2 (14th December 2020) - Cui, Haixia; Hu, Pandeng; Zhang, Yi; Huang, Weiwei; Li, Adan
Abstract: Conjugated carbonyl electrode materials have attracted much attention because of their ability to store various cations, relatively high theoretical capacity, designability, and sustainability. In this Minireview, pyrene‐4, 5, 9, 10‐tetraone (PTO) with four carbonyl functional groups served as the electrode material in secondary batteries. It exhibits excellent electrochemical performance, such as high theoretical specific capacity, high redox potential, and the high utility of active sites. Currently, there are many kinds of optimizations to address the high solubility of PTO in organic electrolytes and improve cycle stability. Forming polymers, immobilizing with carbon materials, changing polarity to form salts, and optimizing electrolytes, such as all‐solid‐state electrolytes, are mainly summarized. We hope this Minireview can provide a guideline for the development of high‐performance secondary batteries using PTO. Abstract : Solubility solutions : This Minireview discusses the electrochemical performance of pyrene‐4, 5, 9, 10‐tetraone (PTO) in secondary batteries and provides some optimizations to solve the high solubility issue in organic electrolytes.